Simulation and wargaming - Turnitsa, Charles; Blais, Curtis; Tolk, Andreas (Wiley, 2022)
"Wargaming is a technique employed in the military, in business, and in other enterprises where planning and risk are part of the decision-making process. In wargaming, as an analytical and decision support approach, a scenario is presented in the form of a formal game. The players of the game will then make decisions based on that scenario, and these will be adjudicated by a referee. The results of that adjudication are then used to illustrate to the players of the game (and to derive insights and lessons learned), based on how effective those decisions are deemed to be."--
Keywords: Kriegsspiel; Computersimulation; War games; Simulation methods; Aufsatzsammlung